La ideología en los pies - González Solas, Javier (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2008)
The one that is assumed like habit constitutes the substratum of our performances, and can have origin in the quotidian, in apparently banal elements to which attention by its naturalization is not lent. Constructed generally by average men for average men (basic mechanism for the culture of masses) makes tehe ideologies “democratics", and that way they establish the final interpretant for a space of concrete knowledge. In the present case the attention is called about the mean level established by mass media for the understanding of Design.